Sharia disclosures: An exploratory study from the perspective of Sharia-compliant companies and professional users. Issue 3 (13th June 2016) - Che Azmi, Anna; Ab Aziz, Norazlin; Non, Normawati; Muhamad, Rusnah
Abstract : Purpose: This paper aims to examine the reasons behind the low level of Sharia -related disclosures, particularly Sharia -compliant companies, to gain an understanding on how these companies disclose Sharia -related information in their annual reports, and how professional users of these reports search for such disclosures. Design/methodology/approach: The study is an exploratory research based on structured interviews with individuals involved in the preparation of annual reports of Sharia -compliant companies and professional users of annual reports. Findings: Most Sharia -compliant companies and professional users interviewed agree that the most relevant Sharia -related information is most commonly understood as the information found in the financial statement and its notes (accounting-related disclosures). Their responses indicate that there is a disjoint between the conventional disclosure practices on corporate social responsibility items and the Sharia -related information. Research limitations/implications: The idea of full disclosure needs to be further understood from the perspectives of Sharia . This study provides insights into the types of Sharia -related information that are important for disclosure. Future research should focus on examining a larger number of companies and interviewing more professional users from different jurisdictions to generate more knowledge about the nature of Sharia information and its disclosure. Practical implications: Users of the Sharia screening methods, especially regulators, such as the Securities Commission Malaysia should encourage the disclosure of the required aspects of Sharia in the annual reports of Sharia -compliant companies, as professional users are interested in this type of information. Originality/value: This study offers insights into the reasons behind low Sharia disclosures in annual reports of Sharia -compliant companies.